The GCaMP3 – A GFP-based calcium sensor for imaging calcium dynamics in the human malaria parasite Plasmodium falciparum - Lucas Borges-Pereira; Bruna R.K.L. Campos; Celia R.S. Garcia (MethodsX, 2014)
Calcium (Ca2+) signaling pathways are vital for all eukaryotic cells. It is well established that changes in Ca2+ concentration can modulate several physiological processes such as muscle contraction, neurotransmitter secretion and metabolic regulation (Giacomello et al. (2007) [1], Rizzuto and Pozzan (2003) [2]). In the complex life cycle of Plasmodium falciparum, the causative agent of human malaria, Ca2+ is involved in the processes of protein secretion, motility, cell invasion, cell progression and parasite egress from red blood cells (RBCs) (Koyama et al. (2009) [3]). The generation of P. falciparum expressing genetically encoded calcium indicators (GECIs) represents an innovation in the study of calcium signaling. This development will provide new insight on calcium homeostasis and signaling in P. falciparum. In addition, these novel transgenic parasites, PfGCaMP3, is a useful tool for screening and identifying new classes of compounds with anti-malarial activity. This represents a possibility of interfering with signaling pathways controlling parasite growth and development. Our new method differs from previous loading protocols (Garcia et al. (1996) [4]; Beraldo et al. (2007) [5]) since: • It provides a novel method for imaging calcium fluctuations in the cytosol of P. falciparum, without signal interference from the host cell and invasive loading protocols. • This technique could also be expanded for imaging calcium in different subcellular compartments. • It will be helpful in the development of novel antimalarials capable of disrupting calcium homeostasis during the intraerythrocytic cycle of P. falciparum.